Emodin Combined with Nanosilver Inhibited Sepsis by Anti-inflammatory Protection - Li, Hong; Yang, Tian; Zhou, Hong; Du, Juan; Zhu, Bo; Sun, Zhongmin (Frontiers in Pharmacology, 2017)
Background: Emodin is the main active component of rhubarb, which has demonstrated many beneficial effects against inflammation. Nanosilver is an effective antimicrobial agent. The present study was designed to observe the effects of Emodin combined with silver nanoparticles (E/S) on sepsis protection and related mechanism. Methods: E/S was prepared by loading different concentrations of Emodin on nanosilver and cytotoxicity of E/S were determined by suphorhodamine B assays. Anti-microbial activities of E/S were assayed by direct interaction with various common pathogens and anti-adhesive activites of E/S on leukocytes with endothelial cells were assayed by biochemical analysis. Next, inflammatory cell enumeration, inflammatory mediators in bronchoalveolar lavage fluid (BALF) and endothelial cell function were analyzed on a clinically relevant model of sepsis induced by cecal ligation and puncture (CLP) after E/S adminstration. The effects of E/S on NF-κB and p38 were also examined by western blot. Results: E/S exhibited little cytotoxicity action on endothelial cells and significant inhibitory activities against all tested common microorganisms and adherence between leukocyte and endothelial cells. E/S induced anti-sepsis protection mainly mediated by inhibition of inflammatory cells infiltration, down-regulation of TNF-alpha, IL-8 and lactic dehydrogenase (LDH), and inhibition of NF-κB and p38 pathways in mice 24 h post-CLP. Conclusion: Our data suggest that E/S has strong anti-sepsis effects, which was related with anti-inflammatory protection and thereby promote survival following sepsis challenge.